Spin pumping and inverse spin Hall effect in antiferromagnetic exchange coupled [Co/Ru/Co]/Pt heterostructures - Aviles Felix, Luis Steven (2017)
We report the observation of spin pumping and inverse spin Hall effects in antiferromagnetically coupled [Co/Ru/Co]/Pt heterostructures. The “spin-flop” magnetization process observed in antiferromagnetically exchange coupled Co layers combined with spin pumping and inverse spin Hall effects allowed us to detect both transversal and longitudinal charge accumulations. By controlling the exchange coupling strength and the spin flop transition in the magnetization process, it was possible to produce spin currents polarized in different directions.